2006
DOI: 10.1007/s00595-006-3267-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Spontaneous Pneumothorax Secondary to Metastatic Angiosarcoma of the Scalp: Report of a Case

Abstract: Angiosarcoma is a highly malignant neoplasm, which most often develops on the scalp or face of elderly people. Common distant metastatic sites include the lung, liver, lymph nodes, and skin. We report a case of angiosarcoma manifesting as simultaneous bilateral spontaneous pneumothorax secondary to pulmonary metastases in an 86-year-old man. The pneumothorax preceded the diagnosis of angiosarcoma. Chest computed tomography showed multiple thin-walled cavitary metastatic pulmonary lesions, which increased in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
0
14
0
2
Order By: Relevance
“…Pneumothorax occurs most frequently with osteosarcomas, although it has been reported in other sarcomatous tumors and in tumors with an aggressive and necrotic nature . Metastatic pulmonary angiosarcomas, especially those arising from the scalp, frequently present with pneumothorax . SP as a complication of primary lung carcinoma is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumothorax occurs most frequently with osteosarcomas, although it has been reported in other sarcomatous tumors and in tumors with an aggressive and necrotic nature . Metastatic pulmonary angiosarcomas, especially those arising from the scalp, frequently present with pneumothorax . SP as a complication of primary lung carcinoma is rare.…”
Section: Discussionmentioning
confidence: 99%
“…2 Metastatic pulmonary angiosarcomas, especially those arising from the scalp, frequently present with pneumothorax. [3][4][5] SP as a complication of primary lung carcinoma is rare. It is estimated that only 2% of all cases of SP coexist with malignant lung diseases, either primary or secondary.…”
Section: Discussionmentioning
confidence: 99%
“…Spontan pnömotorakslar içinde eşzamanlı iki taraflı spontan pnömotoraks oranı birçok çalışmada %1'in altında gösterilirken, bazılarında da %3-8 olarak bildirilmektedir [7][8][9]. Esther ve ark.…”
Section: Discussionunclassified
“…The majority of cases had known lung lesion metastases or had a detectable lung lesion noted shortly after the SBSP occurred. The phenomenon has been reported in cases of metastatic sarcoma, trophoblastic tumor, non-seminomatous testicular cancer, and non-Hodgkin lymphoma [3][4][5][6][7][8][9][10] Sarcoma is most commonly associated with SBSP. One review examining 15 cases of SP after treatment with chemotherapy found an average time to develop SP after initiation of chemotherapy was 2-23 days [7].…”
Section: Discussionmentioning
confidence: 99%